How to enrich team research in healthcare by considering five theoretical perspectives - Seelandt, Julia C.; Boos, Margarete; Kolbe, Michaela; Kämmer, Juliane E. (Frontiers in Psychology, 2023)
The aim of this paper is to inspire team research to apply diverse and unconventional perspectives to study team dynamics and performance in healthcare settings. To illustrate that using multiple perspectives can yield valuable insights, we examine a segment of a team interaction during a heart-surgery, using five distinct interdisciplinary perspectives known from small group research: the psychodynamic, functional, conflict-power-status, temporal, and social identity perspectives. We briefly describe each theoretical perspective, discuss its application to study healthcare teams, and present possible research questions for the segment at hand using the respective perspective. We also highlight the benefits and challenges associated with employing these diverse approaches and explore how they can be integrated to analyze team processes in health care. Finally, we offer our own insights and opinions on the integration of these approaches, as well as the types of data required to conduct such analyses. We also point to further research avenues and highlight the benefits associated with employing diverse approaches. Finally, we offer our own insights and opinions on the integration of these approaches, as well as the types of data required to conduct such analyses.